(untitled) (Czech Journal of International Relations, 2024)
Five Years After the Fall of the Berlín Wall. Paper Presented at the lnternational Summer Course 1995 on National Security. Ed. by Werner Kaltefleiter, Ulrike Schumacher. Conflicts, Options, Strategies in a Threatened World. Vol. 1. Peter Lang Europäischer Verlag der Wissenschaften, Frankfurt am Main- Berlín- Bern- New York- Paris- Wien 1996, 250 stran, ISBN 3-631-30 407-2, US: ISBN 0-8204-3196-6.